Fulwell Bus Depot rest room, 1947 (London, 1947)
1947 1945-1951 "Fulwell Bus Depot rest room, 1947" [BW0213], 1947, Trades Union Congress Women bus workers at Fulwell Bus Station in Twickenham, South London.